A Minimal White-Box Dedicated Cipher Proposal Using Incompressible Lookup Tables: Space-Hard AES - Rodrigues, Félix Carvalho; Dahab, Ricardo; López, Julio; Fujii, Hayato; Serpa, Ana Clara Zoppi (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2023)
In a white-box context, an attacker has full access to the execution environment and the implementation of cryptographic algorithms. Dedicated white-box ciphers, such as WEM and SPNbox, provide incompressibility and key extraction protections in this context, at the cost of increased memory usage and performance loss compared to standard ciphers. Even when a pure white-box threat model is not warranted, the use of incompressible lookup tables can be helpful in deterring side-channel attacks. In this paper we present a simple threat model for such scenarios and propose a dedicated cipher, Space-Hard AES, which provides minimal incompressibility guarantees while presenting better performance for ARMv8 implementations than other dedicated ciphers.